Sci-Hub: What Is It, and Why Does It Matter to Academic Libraries? An Interview with Michael Levine-Clark and Peter Katz: Edited by Eleanor I. Cook. Issue 2 (18th August 2017) - Cook, Eleanor I.; Levine-Clark, Michael; Katz, Peter
ABSTRACT: Piracy of subscription-based scholarly literature has reached a new peak with the advent of Sci-Hub and other sites like it. Sci-Hub is a collection of over 68 million items led by and compiled by a researcher from Kazakhstan. This interview was conducted to gain insights from an academic library director, Michael Levine-Clark, who with other colleagues is doing research on how scholars discover and access research materials. Peter Katz, who works for Elsevier, discusses what Sci-Hub means for him as someone responsible for identifying and blocking activity that sets off alerts in their usage system indicating that the activity may be being undertaken by unauthorized users. These two individuals provide thoughtful observations about what Sci-Hub may mean for the future of article discovery in academic libraries and how Open Access models will impact and influence the dynamic between pirated materials and those found behind a paywall.